(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study examines the influence of business networks, product innovation, and business competition on the development of culinary MSMEs in Kapanewon Banguntapan, Bantul. Culinary MSMEs have an important role in supporting local economic growth, but they face challenges such as weak business networks, limited product innovation, and high market competition. This research applies a quantitative approach using a proportionate stratified random sampling technique, with 209 respondents who are culinary MSME actors in the region. Data were collected through interviews and questionnaires and analyzed using Partial Least Squares Structural Equation Modelling (SEM-PLS) with SmartPLS 3 software. The results indicate that business networks, product innovation, and business competition each have a positive and significant effect on MSME development. Moreover, these three variables simultaneously exert a positive and significant influence on the overall development of culinary MSMEs